Identification of a deubiquitinating enzyme as a novel AGS3-interacting protein. - Zhuojin Xu; Bin Xia; Qiang Gong; Jeffrey Bailey; Benjamin Groves; Monte Radeke; Stephen A Wood; Karen K Szumlinski; Dzwokai Ma (PLoS ONE, 2010)
Activator of G protein Signaling 3 (AGS3) is a receptor-independent G protein activator that has been implicated in multiple biological events such as brain development, neuroplasticity and addiction, cardiac function, Golgi structure/function, macroautophagy and metabolism. However, how AGS3 is regulated is little known. We demonstrate here that AGS3 interacts with a ubiquitin specific protease USP9x, and this interaction is at least partially mediated through the C-terminal G protein regulatory domain of AGS3. Knockdown of USP9x causes a moderate reduction in the level of AGS3. In contrast, overexpression of either USP9x or its deubiquitinating domain UCH increases the amount of AGS3, whereas expression of the mutant UCH domain that lacks deubiquitinating activity does not have the same effect. As previously observed in AGS3 knockdown cells, the localization of several marker proteins of the late Golgi compartments is disturbed in cells depleted of USP9x. Taken together, our study suggests that USP9x can modulate the level of a subpopulation of AGS3, and this modulation plays a role in regulating the structure of the late Golgi compartments. Finally, we have found that levels of AGS3 and USP9x are co-regulated in the prefrontal cortex of rats withdrawn from repeated cocaine treatment. In conjunction with the above data, this observation indicates a potential role of USP9X in the regulation of the AGS3 level during cocaine-induced neuroplasticity.